Hubungan Antara Harga Diri Dengan Impulsive Buying Pada Pegawai Wanita Di Kantor Dinas Perhubungan Kota Surakarta - Reta Lestari, Mega; , Achmad Dwityanto, S.Psi, M.Si (2017)
Shopping to buy of daily needs is a natural thing. But the activity of shopping becomes unnatural when someone makes a purchase only to to buy a wanted things and performed impusif or without prior planning. The purchase process is carried out without planning tend to harm the individual, because usually people who make purchases on impulse will buy goods or products that are not needed. One of the factors of impulse buying is self-esteem. This study aims to (1) determine the relationship between self-esteem with Impulsive buying, (2) determine the level of self-esteem on the employee women in the office department of transportation Surakarta City, (3) determine the level of Impulsive buying employee women in the office department of transportation Surakarta City, (4) determine the effective contribution of the dignity of the impulsive buying. Subjects of research using population studies, that all female employees in the Office of Transportation Surakarta aged 20-40 years. The hypothesis proposed that there is a negative relationship between self-esteem with impulsive buying. Analyzed data using product moment correlation test. Obtained correlation coefficient of -0.225 with a significance of p = 0.040 (p> 0.05), which means there is a significant negative correlation between self-esteem with impulse buying. The effective contribution of the self esteem of the impulsive buying behavior of 5.1%, this means that there are 94.9% of other variables that influence buying impusive, for example marketing, characteristics consumer, and products have the characteristics. Keywords: Self esteem, impulsive buying, employee women